The impact of BDOODE's strategy in acquiring geographic concepts I have average first students (Journal of the College of Basic Education, 2020)
The aim of the research is to find out the effect of the strategy of BDDI on the acquisition of geographical concepts in the first intermediate students. "The number of students in the research sample was (66) students, 33 students for the experimental group, (33) students for the control group, (45) behavioral goals and the number of test paragraphs (45) test paragraphs.The statistical methods used the test t ttest for two independent samples, the Pearson correlation coefficient for the stability coefficient, the Spearman Brown equation. The results showed that the experimental group was better than the control group, which was studied according to the traditional method.